Integrating Edupreneurship and Digital Transformation to Enhance Creative Thinking in Learning Design - Handoko, Hendri; Budi Waluya, Stevanus; Sugiman; Wardono; Vaher, Kristina (APTISI Transactions on Management (ATM), 2025)
The increasing urgency to address climate change has positioned Sustainable Development Goal 13 (Climate Action) as a priority for governments and businesses worldwide. Technological innovations such as Artificial Intelligence (AI), the Internet of Things (IoT), and Blockchain have emerged as transformative tools for reducing environmental impacts, improving energy efficiency, and promoting ethical and sustainable business practices. However, the extent to which these technologies contribute to climate action remains underexplored. This study aims to investigate the role of AI, IoT, and Blockchain in helping businesses achieve SDG 13 by optimizing resources, reducing waste, and enhancing supply chain transparency. A mixed-methods approach was adopted, combining qualitative and quantitative techniques. Semi-structured interviews were conducted with key stakeholders from businesses implementing these technologies, while a survey of 150 businesses was administered to capture broader adoption patterns. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The findings reveal that AI and IoT have significant positive effects on energy management and sustainability outcomes, while Blockchain plays a supportive role by improving transparency and ethical practices, though its adoption remains limited. The combined integration of these technologies yields the most substantial impact. This study concludes that businesses should adopt a holistic strategy to fully leverage technological innovations for advancing SDG 13 and combating climate change.